The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1017/s1357729800015642
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ewe live weight and body condition score around mating on production from four sheep breeds in extensive grazing systems in Uruguay

Abstract: Ewe live iveights were recorded 4 weeks prior to mating, at the beginning of mating and 22 to 23 days later over a period of 3 years in a flock of some 300 breeding ewes comprising approximately equal numbers of Australian Merino, Ideal (Polwarth), Merilin and Corriedale breeds in a pastorally based grazing system in Uruguay. Multiple-bearing ewes were generally heavier than single-bearing ewes which in turn were heavier than ewes which did not conceive, these differences being greatest in 3-and 4-year-old ewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Similarly, Romney and Kivircik ewes of BCS of 2.0 and 2.5, respectively, at breeding, were more likely to get pregnant than ewes of lower BCS (Kenyon et al 2004b;Yilmaz et al 2011). Analysing the same issue another way, pregnant ewes had a higher mean BCS than their non-pregnant counterparts in Kurdi (Esmailizadeh et al 2009) and in various breeds (Gonzalez et al 1997). In manipulative studies, Gunn & Doney (1979) reported that when Cheviot ewes were fed to maintain a set BCS, those ewes with a BCS of 3.0 had higher pregnancy rates at first mating than ewes with a BCS of 2.0.…”
Section: Pregnancy Ratesmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Romney and Kivircik ewes of BCS of 2.0 and 2.5, respectively, at breeding, were more likely to get pregnant than ewes of lower BCS (Kenyon et al 2004b;Yilmaz et al 2011). Analysing the same issue another way, pregnant ewes had a higher mean BCS than their non-pregnant counterparts in Kurdi (Esmailizadeh et al 2009) and in various breeds (Gonzalez et al 1997). In manipulative studies, Gunn & Doney (1979) reported that when Cheviot ewes were fed to maintain a set BCS, those ewes with a BCS of 3.0 had higher pregnancy rates at first mating than ewes with a BCS of 2.0.…”
Section: Pregnancy Ratesmentioning
confidence: 98%
“…Furthermore, BCS, in comparison with live weight, circumvents the issues of skeletal size between and within breeds and physiological state (i.e. pregnancy) and is not influenced by gut fill or the length and wetness of the fleece (Jefferies 1961;Adalsteinsson 1979;Russel 1984a, b;Gonzalez et al 1997;Esmailizadeh et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Sampling dates were selected because they were prior to mating, a period considered key for the proper nutrition of animals as preparation for reproduction. It has been shown that nutrition during the weeks before mating has an important effect on ovulation and lambing rates (González et al 1997).…”
Section: Sampling and Measurementsmentioning
confidence: 99%
“…Several authors have shown an association between nutritional status and ovulation rates in sheep and red deer (Gonzalez et al, 1997;Gunn et al, 1969;Langvatn et al, 1996;Russel, 1971). Higher EVI during fall e winter, could be thus associated to better nutritional status of ewe at mating and thus higher probabilities of ovulation and conception.…”
Section: Discussionmentioning
confidence: 99%